Use of Evaporative Cooling Systems and Their Effects on Core Body Temperature and Lying Times in Lactating Dairy Cattle - Jared R. Johnson; Michael Brouk; L. Mendonca; J. P. Harner (Kansas Agricultural Experiment Station Research Reports, 2015)
A study was performed to assess the effect of an evaporative cooling system on respiration rates, rear udder temperature (Tu), core body temperature (CBT), and resting time in lactating dairy cows. Cows were divided into two treatment groups and rotated between two facilities. Cows were either housed in a bedded pack barn (PACK) equipped with an evaporative cooling system (Cyclone fans, Chippewa Falls, WI) or a tie-stall barn (TIE) equipped with cooling cells. Cows housed in PACK had two cooling treatments: FAN (Cyclone fans only, no fog); and FANFOG (Cyclone fans and fog on). Groups of cows rotated between TIE and PACK every 8 hours, and effects of housing as well as cooling treatment within PACK were analyzed. During FANFOG, PACK cows had a reduction (P<0.05) in respiration rate (breaths per minute) in comparison to TIE (69 vs 76 ± 2.4 BPM). Breaths per minute also increased significantly throughout the day for TIE but this was not the case for PACK. No differences were found in Tu between treatments. While exposed to the FANFOG environment, cows spent decreased time above 102.2°F CBT when compared to FAN. Cows housed in PACK during FAN and FANFOG also spent fewer hours/ day above 102.2°F CBT vs TIE. Cows housed in TIE showed numerically greater total daily lying times during FAN and FANFOG compared to cows housed in PACK, although these results were not significant. These results confirm that evaporative cooling systems (Cyclone fans and fog) are effective at decreasing respiration rates and CBT, while having no effect on Tuand lying times in lactating dairy cows.
Keywords: heat stress; evaporative cooling; core body temperature; lying behavior